Environmental Ethics in the Novel Tetralogy Eye Okky Madasari's Works a Study of Literature Ecology - Sinaga, Herlin Nadia; Gustianingsih, Gustianingsih; Harahap, Nurhayati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Environmental ethics discusses moral norms and rules that regulate human behavior in dealing with the environment. The novel Mata Tetralogy highlights the moral message of maintaining harmony with the environment. This research aims to describe environmental ethics in the novel Tetralogi Mata by Okky Madasari so that the theoretical views of anthropocentrism, biocentrism and ecocentrism can be seen. These three theories have different views regarding the relationship between humans and the entire universe. The method used is descriptive qualitative describing data through words to obtain research data sourced from Okky Madasari's Novel Tetralogi Mata. Data collection techniques start from reading the novel repeatedly and marking and recording the data found. After data related to environmental ethics is collected, it will be applied in discussing the problem. This research uses a study of literary ecology proposed by Endraswara, namely the science that studies how humans adapt and protect the environment well. The research results of these four novels show that anthropocentrism is seen through the characters' attitudes which prioritize human interests over nature, without considering the sustainability of the ecosystem. The biocentrism view prioritizes the intrinsic value of every living creature and is reflected in the actions of figures who respect animal rights and maintain the continuity of their habitat, and the ecocentrism view which includes respect for biotic and abiotic elements in the ecosystem, such as soil, water and rocks.